Endovascular Repair of Iatrogenic Aortic Rupture. Issue 5 (28th July 2013) - Lo, Casey; Galvin, Sean D.; Barnett, Stephen; Seevanayagam, Siven
Abstract Thoracic endovascular aortic repair (TEVAR) has been used for traumatic and acute spontaneous rupture of the descending thoracic aorta with good results. We present the case of a 40‐year‐old male whose thoracic spinal prosthesis eroded through the descending thoracic aorta; the aortic disruption was successfully managed with emergent deployment of an endovascular stent. doi: 10.1111/jocs.12162 (J Card Surg 2013;28:561–563)